Virulence and genome analysis of three historical Francisella tularensis ssp. holarctica isolates for development of a Type B test panel - Mlynek, Kevin D.; Richardson, Joshua B.; Martinez, Elsie E.; Toothman, Ronald G.; Qiu, Ju; Cline, Curtis R.; Bozue, Joel A. (Frontiers in Cellular and Infection Microbiology, 2025)
Francisella tularensis ssp. tularensis (Type A) and ssp. holarctica (Type B) are the etiological agent of tularemia. Most studies on F. tularensis pathogenesis and vaccine development have focused on the Type A Schu S4 strain. However, Type B isolates remain less understood, emphasizing the need for further research. To address this concern and provide well characterized Type B isolates to test future vaccine efficacy, we selected three Type B isolates available in the USAMRIID repository (VT68, strain 425, and strain 503). These strains were chosen based on the original isolation source, the availability of historical in vivo data, and genomic sequence data. Strains were characterized for extracellular and intracellular growth, lipopolysaccharide profile via western blot analysis, and LD50 values were determined by both murine intranasal challenge and aerosolization of Fischer 344 rats. Strain 425 displayed several attenuation indicators and was completely attenuated in a rat aerosol challenge model. In contrast, VT68 and 503 remained highly virulent in rodent models but displayed some differences in lesion severity. Although F. tularensis genomes are known to be highly conserved, genomic analysis revealed multiple inversions and 68 unique genetic differences among these three Type B isolates. From this study, we were able to provide well-characterized Type B F. tularensis strains to test future vaccines and therapeutics.